The Harvest of Beluga Whales in Canada's Western Arctic: Hunter-based Monitoring of the Size and Composition of the Catch - Harwood, Lois A.; Norton, Pamela; Day, Billy; Hall, Patricia A. (ARCTIC, 2002)
Hunter-based beluga monitoring programs, in place in the Mackenzie Delta since 1973 and in the Paulatuk, Northwest Territories, area since 1989, have resulted in collection of data on the number of whales harvested and on the efficiency of the hunts. Since 1980, data on the standard length, fluke width, sex, and age of the landed whales have also been collected. The number of belugas landed each year averaged 131.8 (SD 26.5, n = 1337) between 1970 and 1979, 124.0 (SD 23.3, n = 1240) between 1980 and 1989, and 111.0 (SD 19.0, n = 1110) between 1990 and 1999. The human population increased during this same period. Removal of belugas from the Beaufort Sea stock, including landed whales taken in the Alaskan harvests, is estimated at 189 per year. The sex ratio of landed belugas from the Mackenzie Estuary was 2.3 males:1 female. Median ages were 23.5 yr (47 growth layer groups [GLG]) for females (n = 80) and 24 yr (48 GLG) for males (n = 286). More than 92% of an aged sample (n = 368) from the harvest consisted of whales 10 or more years old (20 GLG). The rate of removal is small in relation to the expected maximum net productivity rate of this stock. The continued availability of large, old individuals after centuries of harvesting and the apparent lack of change in the size and age structure of the catch in recent years also support a conclusion that the present level of harvest is sustainable. Des programmes de surveillance du bélouga gérés par les chasseurs et mis en oeuvre dans le delta du Mackenzie depuis 1973 et dans la région de Paulatuk (Territoires du Nord-Ouest) depuis 1989, ont abouti à la collecte de données sur le nombre de baleines blanches prélevées et sur l'efficacité des expéditions de chasse. Depuis 1980, on a également collecté des données sur la longueur standard, la largeur de la nageoire caudale, le sexe et l'âge des bélougas ramenés à terre. Le nombre moyen de bélougas ramenés à terre chaque année était de 131,8 (écart-type 26,5, n = 1337) entre 1970 et 1979, de 124,0 (écart-type 23,3, n = ...